MAKNA RUANG DALAM BUDAYA MASYARAKAT SIKKA - Kian, Donatus Ara; Rayawulan, Robertus M.; Mberu, Yuliana; Lily, Budhi B. (Jurnal Arsitektur Komposisi, 2018)
Abstract: The essence of human existence depends on the environment and fellow humans. The activity of human life takes place in space and to show its existence human beings always create space, so that there is a process of human settlement in a certain place. The culture of settling in the people of East Nusa Tenggara creates certain patterned settlements. The phenomenon of living culture-based occurs in the Sikka community. Space philosophy emerged in the process of building houses and villages in the Sikka community. This paper presents the meaning of space in the culture of the settlements of the Sikka community. Research carried out with a qualitative paradigm, presented descriptively and associated with relevant literature. As a result, the culture settled and built the residence of the tribes within the village (Wisung-wagang), kampung, magical concepts (Lero and kala), and Amerta were closely related to the concepts and meaning of space according to the culture of the Sikka community.Keywords:space, culture, house, Sikka communityAbstrak: Hakekat keberadaan manusia bergantung pada lingkungan dan sesama manusia. Aktivitas kehidupan manusia berlangsung dalam ruang dan untuk menunjukkan eksistensinya manusia selalu menciptakan ruang, sehingga terjadi proses bermukim manusia pada tempat tertentu. Budaya bermukim pada masyarakat Nusa Tenggara Timur menciptakan permukiman berpola tertentu. Fenomena bermukim berbasis budaya terjadi di kalangan masyarakat Sikka. Filosofi ruang muncul pada proses pembangunan rumah maupun kampung di kalangan masyarakat Sikka. Tulisan ini memaparkan makna ruang dalam budaya bermukim masyarakat Sikka. Penelitian dilakukan dengan paradigma kualitatif, disajikan secara deskriptif dan dikaitkan dengan pustaka yang relevan. Hasilnya, budaya bermukim dan membangun tempat kediaman suku-suku dalam kampung (Wisung-wagang), kampung, konsep magis (Lero dan kala), dan Amerta berkaitan erat dengan konsep dan makna ruang menurut budaya masyarakat SikkaKata kunci; ruang, budaya, rumah, masyarakat Sikka